Advanced reactor concepts (ARC) : a new nuclear power plant perspective producing energy /: a new nuclear power plant perspective producing energy. (2023) - Zohuri, Bahman; Balgehshiri, Seyed Kamal Mousavi; Paydar, Ali Zamani
No abstract available